Preventing Sexual Abuse in Congregations: A Resource for Leaders - McClintock, Karen A. (Rowman & Littlefield Publishers, 2004)
Are you ready to abuse-proof your congregation? If one child or adult is spared the confusing ordeal of unwanted touch, it will be worth your time to read this book. In this comprehensive resource, Methodist pastor and pastoral psychologist Karen McClintock demonstrates that sexual abuse in congregations is preventable and gives clergy and lay leaders the tools they need to prevent it. This book shows congregations how to protect children and vulnerable adults, prevent sexual harassment either by clergy or of clergy, and strengthen clergy families by raising awareness of the occupational and emotional risks inherent in pastoral ministry. When you have finished this book, you will be familiar with the conditions in parishes and in the mental health of the individuals within them that lead to risky behaviors. You will be equipped to recognize and set sexual boundaries for yourself and to open dialogue about these issues in your congregation. You will have laughed at, celebrated, and honored human sexual power, pleasure, and vulnerability. You will have gained the knowledge you need, and perhaps the courage, to communicate these ideas within your congregation so that children and vulnerable adults are protected.